Understanding the Mindanao Conflict (Patricio P. Diaz) - Layador, Maria Anna Rowena Luz (Kasarinlan: Philippine Journal of Third World Studies; Vol 19 No 1 (2004): Human Security in Conflict Situations, 2007)
Reviw of Understanding the Mindanao Conflict by Patricio P. Diaz.
Keywords: Mindanao; Conflict